The mechanization of the heart Harvey and Descartes - Fuchs, Thomas 1958- (University of Rochester Press, 2001)
In Mechanization of the Heart: Harvey and Descartes Thomas Fuchs discusses the similarities and differences of the views of the two seventeenth-century scholars William Harvey and Rene Descartes on the beart and circulationof the blood; Fuch traces the reception of the two views in the medical literature of the time and the influence both views had.
Keywords: Descartes, René, -- 1596-1650.; Harvey, William, -- 1578-1657.